Slipped upper femoral epiphysis: Outcome after in situ fixation and capital realignment technique - Arora, Sanjay (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Slipped upper femoral epiphysis (SUFE) is the gradually acquired malalignment of the upper femoral epiphysis (capital) and the proximal femoral metaphysis. SUFE is uncommon in India, and there are no previous studies on outcome and clinical characteristics of patients with SUFE from India. This study evaluates the presentation, disease associations and outcome of SUFE from a tertiary care centre in India. MATERIALS AND METHODS: Twenty six consecutive children with SUFE seen over a period of 4 years were reviewed. The clinical presentations, severity of the slip, surgical interventions (n=30) were assessed. Twenty one boys and five girls with a mean age 13.1 years (range 10-16 years) were included in the study. Four children had bilateral involvement. There were 4 rural and 22 urban children from the eastern and southern states of the country. The presentation was acute in 7, acute on chronic in 5, and chronic in 14, with a mean duration of symptoms of 51 days (range 3-120 days). Slips were stable in 16 and unstable in 10 children. Two children had adiposogenital syndrome. Body mass index was high in 12 out of 23 children. Vitamin D levels were low in 20 out of 21 children, with a mean vitamin D level of 12.61 ± 5 ng/ml. Eighteen children underwent in situ pinning. Eight children underwent capital realignment. RESULTS: Clinical outcome as assessed by Merle d’ Aubigne score was excellent in 6, good in 10, fair in 6 and poor in 1. Half of the in situ fixation patients underwent osteoplasty procedure for femoroacetabular impingement and 5 more were symptomatic. The head neck offset and α angle after in situ pinning were −1.12 ± 3 mm and 66.05 ± 9.7°, respectively and this improved to 8.7 mm and 49°, respectively, after osteoplasty. One child in the pinning group had chondrolysis. Eight patients with severe slip underwent capital realignment. Mean followup was 20.15 months. The anterior head neck offset and α angle were corrected to 6.8 ± 1.72 mm and 44.6 ± 7.0° mm, respectively. Two children with unstable slip in the capital realignment group had avascular necrosis which was diagnosed at presentation by bone scan. CONCLUSION: High BMI, vitamin D deficiency and endocrine disorders are associated with SUFE in India and should be evaluated as some of these are amenable to prevention and treatment. Most patients treated with in situ pinning developed femoroacetabular impingement. The early results after capital realignment procedure are encouraging and help to avoid a second procedure which is needed in a majority of patients who underwent in situ pinning.